2017
DOI: 10.1128/jvi.00736-17
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Rta-Mediated Accumulation of DNA Methylation Interferes with CTCF Binding in both Host and Viral Genomes

Abstract: Rta, an Epstein-Barr virus (EBV) immediate-early protein, reactivates viral lytic replication that is closely associated with tumorigenesis. In previous studies, we demonstrated that in epithelial cells Rta efficiently induced cellular senescence, which is an irreversible G 1 arrest likely to provide a favorable environment for productive replications of EBV and Kaposi's sarcoma-associated herpesvirus (KSHV). To restrict progression of the cell cycle, Rta simultaneously upregulates CDK inhibitors and downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Entry of EBV into cells does not use xCT. A small upregulation of SLC7A11 occurred in EBV-negative 293 cells exogenously expressing the EBV lytic transactivator protein RTA [ 39 ]. Changes in SLC7A11 gene expression occur during primary EBV infection when B cells are reprogrammed and thousands of genes are regulated [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Entry of EBV into cells does not use xCT. A small upregulation of SLC7A11 occurred in EBV-negative 293 cells exogenously expressing the EBV lytic transactivator protein RTA [ 39 ]. Changes in SLC7A11 gene expression occur during primary EBV infection when B cells are reprogrammed and thousands of genes are regulated [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is speculated that the absence of SLC5A8 expression is largely influenced by dense methylation in this block of 20 CpG dinucleotides. Along these CpGs, a computational prediction using the Genomatix software (https://genomatix.de/) identified the consensus binding sites for the methylation-sensitive transcription factor E2F and transcriptional repressor CTCF (34,35); however, further experiments are required to determine the role of these transcription factors in the regulation of SLC5A8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have revealed that CTCF can regulate viral gene expression in other double-stranded DNA viruses. For instance, in Kaposi’s sarcoma herpesvirus (KSHV) [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], herpes simplex virus (HSV) [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ] and human cytomegalovirus (CMV) [ 90 ], CTCF has been shown to bind to the viral genome and regulate viral gene expression by modulating the accessibility of the viral genome to transcription factors. Finally, it has also been suggested that viruses can modulate CTCF activity to promote viral replication.…”
Section: Ebv and Ctcfmentioning
confidence: 99%